The degree to which school principals in Muscat Governorate practice transformational leadership in light of the gender variable, from the teachers' perspective (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to measure the degree to which school principals in Muscat Governorate, Sultanate of Oman, practice transformational leadership from the perspectives of teachers, across all four dimensions of transformational leadership. The study employed a descriptive-analytical approach and utilized a questionnaire as the data collection tool, which was administered to a sample of 501 male and female teachers.The study concluded that the extent to which school principals in Muscat Governorate apply transformational leadership styles was high across the overall dimension, with an average score of 4.17, and high across all four dimensions. Furthermore, the results indicated no statistically significant differences at the 0.05 level in the average application of transformational leadership principles by school principals in Muscat Governorate attributable to the gender variable. The study recommended the necessity of strengthening the transformational leadership approach in training programs.
Keywords: School Principals; Transformational Leadership; Gender Variable; Muscat Governorate; Teachers